2021
DOI: 10.1128/aac.01264-21
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Activity against Unusual Clinically Significant Gram-Negative Pathogens

Abstract: The minocycline susceptibility of 3,856 isolates including Burkholderia , Achromobacter , Alcaligenes, Aeromonas , and Stenotrophomonas maltophilia from the SENTRY surveillance (2014-2019) were analyzed. The susceptibilities of these species (number; %S) were Achromobacter spp. (n=411; 92.6%), Burkholderia cepacia species complex (n=19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There is limited international data about the use of colistin S. maltophilia infections. Even though minocycline and tigecycline have low minimal inhibitory concentrations among S. maltophilia isolates [ 34 , 35 , 42 ] and some studies have shown clinical outcomes comparable to TMP-SMX [ 43 ], 65% of the isolates in our study had a tigecycline MIC of ≥ 4 μg/ml. They were considered non-susceptible using interpretive criteria for Enterobacteriaceae [ 9 , 44 ].…”
Section: Discussionmentioning
confidence: 64%
“…There is limited international data about the use of colistin S. maltophilia infections. Even though minocycline and tigecycline have low minimal inhibitory concentrations among S. maltophilia isolates [ 34 , 35 , 42 ] and some studies have shown clinical outcomes comparable to TMP-SMX [ 43 ], 65% of the isolates in our study had a tigecycline MIC of ≥ 4 μg/ml. They were considered non-susceptible using interpretive criteria for Enterobacteriaceae [ 9 , 44 ].…”
Section: Discussionmentioning
confidence: 64%
“…Due to its toxicity, chloramphenicol is rarely used. We tested tigecycline, a derivative of minocycline, which appears to demonstrate a good activity against Achromobacter (MIC 50 = 0.5 mg/L and 1 mg/L for tigecycline and minocycline, respectively) [33,34]. Overall, clinical studies are needed to make recommendations for the treatment of Achromobacter, and more generally of non-fermenters, especially considering the increase in their prevalence and the recent availability of new antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…As Achromobacter, other non-fermenting Gram-negative bacilli, such as Stenotrophomonas maltophilia, Burkholderia cepacia complex, Pandoraea or Cupriavidus are increasingly isolated from the respiratory tract of PWCF and are characterised by their high resistance to antibiotics. For all these bacteria, SXT and tetracycline (minocycline) are among the most active antimicrobial agents [8,22,[34][35][36][37][38]. For most of them, carbapenems represent one of the most active antimicrobial agents except for S. maltophilia, which is intrinsically resistant due to a chromosomal carbapenemase.…”
Section: Discussionmentioning
confidence: 99%